Computers in Administration: A Fortran IV Introduction. - Powell, John E. (The Accounting Review, 1974)
Reviews the book "Computers in Administration: A Fortran IV Introduction," by Robert E. Malcom, Malcolm H. Gotterer, and Frank Luh.